The Crucial Role of Demannosylating Asparagine-Linked Glycans in ERADicating Misfolded Glycoproteins in the Endoplasmic Reticulum - Zhang, Jianjun; Wu, Jiarui; Liu, Linchuan; Li, Jianming (Frontiers in Plant Science, 2021)
Most membrane and secreted proteins are glycosylated on certain asparagine (N) residues in the endoplasmic reticulum (ER), which is crucial for their correct folding and function. Protein folding is a fundamentally inefficient and error-prone process that can be easily interfered by genetic mutations, stochastic cellular events, and environmental stresses. Because misfolded proteins not only lead to functional deficiency but also produce gain-of-function cellular toxicity, eukaryotic organisms have evolved highly conserved ER-mediated protein quality control (ERQC) mechanisms to monitor protein folding, retain and repair incompletely-/mis-folded proteins, or remove terminally misfolded proteins via a unique ER-associated degradation (ERAD) mechanism. A crucial event that terminates futile refolding attempts of a misfolded glycoprotein and diverts it into the ERAD pathway is executed by removal of certain terminal 1,2mannose (Man) residues of their N-glycans. Earlier studies were centered around an ER-type 1,2-mannosidase that specifically cleaves the terminal 1,2Man residue from the B-branch of the three-branched N-linked Man9GlcNAc2 (GlcNAc for N-acetylglucosamine) glycan, but recent investigations revealed that the signal that marks a terminally misfolded glycoprotein for ERAD is an N-glycan with an exposed 1,6Man residue generated by members of a unique folding-sensitive 1,2-mannosidase family known as ER-degradation enhancing -mannosidase-like proteins (EDEMs). This review provides a historical recount of major discoveries that led to our current understanding on the role of demannosylating N-glycans in condemning irreparable misfolded glycoproteins into ERAD. It also discusses conserved and distinct features of the demannosylation processes of the ERAD systems of yeast, plants, and mammals.